What is the role of universities at a time of climate and ecological crisis? - James G. Dyke; George Monbiot (Geo: Geography and Environment)
Abstract This paper presents a dialogue between a writer and an academic about the roles and responsibilities of universities with respect to the climate and ecological crisis. The discussion addressed  six priority issues: education; student protest; academic objectivity; student debt and financing; fossil fuel funding; consensus and risks. In considering these issues, the importance of interdisciplinarity was stressed. This included fostering inclusive approaches beyond natural sciences while recognising the importance of different perspectives on environmental challenges. The role of universities as a locus of social change was emphasised. An exploration of opportunities and barriers towards facilitating such perspectives within higher education was discussed.